The Effect of Coffee Chain Customers’ Need to Smell on Their Taste Evaluations - Tuna, Murat Fatih; ÇAM, Selim (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This paper aims to investigate whether ambient scent in coffee chains affects the taste perceptions of customers who consume the products of those chains. The paper highlights the importance of smell in creating memorable experiences and its role in arousing customers. It also mentions the olfactory system’s vital functions in warning and protection, eating behavior, and social communication. The use of ambient scent enhances the memorability of brand-related olfactory information. Regarding taste evaluation, the paper mentions that it involves both objective and subjective processes. Biological preferences and existing information can influence taste perceptions. Positive sensory experiences lead to positive attitudes and increased consumption, while negative experiences can have the opposite effect. The paper also emphasizes the connection between smell and taste, with smell being responsible for a significant portion of what we taste. The ambiance of the coffeehouse and the scent of coffee can influence taste and consumer choices. The sample covers data collected from 578 participants via convenience sampling method. Overall, the paper provides insights into the impact of smell and taste evaluation mediated by customer loyalty in the context of coffeehouse chains. The study is also thought to guide studies on senses other than smell and taste in sensory marketing.